The Roles of the Griot in the Future of Mali: A Twenty-First-Century Institutionalization of a Thirteenth-Century Traditional Institution. (3rd April 2017) - Hoffman, Barbara G.
Abstract: Every ethnic group in Mali has at least one social category of specialists in conflict mediation and resolution. These are casted groups whose duties include the maintenance of a moral as well as structural social order, even in times of great turmoil. Recent research on the activities of these actors shows that the role of traditional mediator has not vanished, but it has evolved through bureaucratic institutionalization. A thickly described case study of the formation of RECOTRADE, the largest nongovernmental organization of traditional communicators in West Africa, demonstrates how this traditional institution is keeping pace with the political and civil development of the country. Résumé: Chaque groupe ethnique au Mali possède au moins une catégorie sociale de spécialistes en médiation et résolution de conflits. Ce sont des groupes de castes dont les fonctions comprennent le maintien d'un ordre social moral et structurel, même durant des moments de grandes agitations. Des recherches récentes sur les activités de ces acteurs montrent que le rôle du médiateur traditionnel n'a pas disparu, mais qu'il a évolué grâce à une institutionnalisation bureaucratique. Une étude de cas très répandue sur la formation de RECOTRADE, la plus grande organisation non gouvernementale de communicateurs traditionnels en Afrique de l'Ouest, montre comment cette institution traditionnelle suit le rythme du développement politique et civil du pays.